IMPROVING THE PRACTICE OF EFFICIENCY AUDIT OF THE AGENT OF THE INSTITUTE OF CONTROL BY THE LEGISLATIVE BRANCH OF GOVERNMENT - Kulyk, Nataliia (Social Economics, 2020)
The article is devoted to the study of the efficiency and effectiveness of the Accounting Chamber of Ukraine’s audit of efficiency as a type of external public financial control. In the course of the research is given the normative-legal base which regulates the activity of the ACU, the principles of conducting the performance audit guided by the agent are analyzed, and the principles of ISSAI 300 are given as an example of international experience. An analysis of the annual report of the Accounting Chamber for 2019 is made, identified the results of control, the structure of inefficient management of budget funds and statistical indicators of implementation of the recommendations been provided. Two performance audits conducted in the ministries were analyzed (Audit of the efficiency of the use of state budget funds allocated to the Ministry of Health of Ukraine for training of medical and pharmaceutical personnel by higher educational institutions, and Audit of the effectiveness of the Ministry of Education and Science of Ukraine), which became the basis for consideration of negative factors in the conduct of AU, which reduce the effectiveness of control. The main indicators of the ACU’s activity for three years (2017-2019) were also considered, the indicators of TSCPF (volume of the subject of control) and SA (volume of actually checked state funds) were demonstrated. The results of the study have shown the main shortcomings in the performance audit of this agent of the Institute of Control, where the focus is the lack of scientific and methodological approaches, which causes uncertainty in the implementation of this type of audit; also non-compliance of the liability which was covered by the audited public funds has been shown; the need to increase the number of ACU employees was identified, the problem of reimbursement of expenses and losses caused by public finances, which are currently carried out due to the lack of coercion, was outlined. Proposals have been developed to improve the effectiveness and efficiency of performance audits, which are to introduce a methodology for conducting performance audits, staff of ACUs being expanded and the recommendations provided after the control being revised. It will be appropriate to introduce international practice of organizing this type of public external financial control, supported by the positive experience of high-performance control over the use of public finances.